Botryopera daleki Renaudie and Lazarus 2013 - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Zenodo, 2022)
Botryopera? daleki Renaudie and Lazarus, 2013a Plate 6, Figs. 5A – 9B. Lophophaenoma sp. M, Petrushevskaya, 1971, pl. 63, figs. 3–4. Botryopera? daleki n. sp., Renaudie and Lazarus, 2013a, pl. 6, figs. 1A–C, 4A–6B; Pl. 8, figs. 1–2B, 5. unknown plagonid group C sp 63, Trubovitz et al., 2020, supplementary data 7. Remarks. In the EEP, specimens vary widely in their degree of silicification. In general, specimens older than ~12Ma tend to be more heavily silicified; however, the degree of silicification can vary even within a single sample. Specimens 7 and 9 we consider to be questionably assigned to this species as they are substantially more silicified than the type material designated by Renaudie and Lazarus (2013a). Additional specimens will be needed to show that differing degrees of silicification should be accepted within the range of this species, or that there is a clear break between the two morphotypes justifying separate species. Range. In the Southern Ocean, this species is rare in the Early Miocene and sporadic from the Middle to Late Miocene. In the EEP, it is present from the Middle to Late Miocene, but the lower limit was not determined (see Table 1). Petrushevskaya’s specimen is from the Middle Miocene equatorial Pacific. Published as part of Trubovitz, Sarah, Renaudie, Johan, Lazarus, David & Noble, Paula, 2022, Late Neogene Lophophaenidae (Nassellaria, Radiolaria) from the eastern equatorial Pacific, pp. 1-158 in Zootaxa 5160 (1) on page 27, DOI:10.11646/zootaxa.5160.1.1, http://zenodo.org/record/10544058